Analisis Tingkat Kepuasan Pengguna Terhadap Pelayanan Parkir Di Fakultas Vokasi Universitas Negeri Surabaya - Muhammad Faiz Maulana (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Parking services are one of the supporting facilities that play an important role in supporting academic activities in higher education environments. The increasing number of students and vehicles at the Faculty of Vocational Studies, State University of Surabaya, has made the need for safe, comfortable, and well-organized parking services increasingly important. This study aims to analyze user satisfaction levels toward parking services at the Faculty of Vocational Studies, State University of Surabaya and to identify service attributes that should be prioritized for improvement. The research employed the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. Data were collected through questionnaires distributed to parking facility users, including students, lecturers, and administrative staff. The results showed that the Customer Satisfaction Index (CSI) value was 69.10%, indicating that users were generally satisfied with the parking services provided. Based on the IPA analysis, six attributes were identified as top priorities for improvement (Quadrant A), namely CCTV availability, Smart Parking implementation, parking arrangement according to parking markings, parking management during peak hours, parking capacity, and parking marking clarity. Meanwhile, attributes such as parking area lighting, pavement condition, staff friendliness, vehicle security, and ease of access to parking entrances and exits were classified into Quadrant B and should be maintained. The findings indicate that the tangible dimension remains the primary aspect requiring improvement to enhance service quality and user satisfaction. Therefore, the parking management is recommended to increase CCTV coverage, implement a Smart Parking system, improve parking capacity, and optimize parking organization to provide more effective, safe, and efficient parking services.